HOW IS POLITICAL BEHAVIOR IN DECISION-MAKING? ORGANIZATIONAL CULTURE PERSPECTIVE IN GOVERNANCE - Lambelanova, Rossy; Saputra, Romi; Nurfurkon, Ardika (Jurnal Politik Pemerintahan Dharma Praja, 2024)
This article discusses political behavior in the context of decision-making from an organizational culture perspective. Political behavior is a complex and common phenomenon in organizational environments, including the decision-making process within them. This research uses a qualitative research method by trying to analyze based on interviews to obtain answers to problems in the field and uses bibliometric analysis which produces 132 literature sources and 5 important aspects in decision making through a collection of literature from Scopus data. Organizational culture plays an important role in shaping and influencing political behavior. By understanding the relationship between political behavior and organizational culture, it is hoped that this article can provide useful insights for practitioners and decision-makers in understanding and managing political behavior that occurs in the context of organizational decision-making. This study found five aspects that must be considered in decision-making, namely the Role and Influence of Leaders, Coalition Building, Public Participation, Personal Relationships and Organizational Culture. From these five aspects, there are several efforts made by the Semarang city government towards political behavior in decision making associated with good organizational culture, which adds value to the effectiveness and implementation of the decision-making process in the Semarang city government.